Utilization of brewer’s spent grain and mushrooms in fortification of smoked sausages - NAGY,Melinda (2017)
Abstract The aim of this study was to obtain alternative types of smoked sausage by using some vegetable raw materials rich in protein. To this end, smoked sausages with brewer’s spent grain [1.5, 3, and 6% w/w], smoked sausages with mushrooms [10, 17, and 30% w/w], and smoked sausages with mixtures of brewer’s spent grain-mushrooms [3/8% and 1.5/16% w/w] were prepared. Three of these formulations were selected based on panellist’s preference, one for each assortment, and stored under darkness at 4°C and 49% relative humidity for 15 days. Smoked sausage samples were collected at three different storage times (T0, initial state; T1, at day 7 of storage; T2, at day 15 of storage) and evaluated from the physicochemical and microbiological point of view to determine their stability during the intended storage period. Regardless of the type of assortment, storage time had a significant influence on the physicochemical and microbiological properties of smoked sausages. Among all samples, the smoked sausage with a mixture of 3% brewer’s spent grain and 8% mushrooms was the most appreciated by the panellists.